Polymer-Drug Conjugate, a Potential Therapeutic to Combat Breast and Lung Cancer - Sibusiso Alven; Xhamla Nqoro; Buhle Buyana; Blessing A. Aderibigbe (MDPI AG, 2020)
Cancer is a chronic disease that is responsible for the high death rate, globally. The administration of anticancer drugs is one crucial approach that is employed for the treatment of cancer, although its therapeutic status is not presently satisfactory. The anticancer drugs are limited pharmacologically, resulting from the serious side effects, which could be life-threatening. Polymer drug conjugates, nano-based drug delivery systems can be utilized to protect normal body tissues from the adverse side effects of anticancer drugs and also to overcome drug resistance. They transport therapeutic agents to the target cell/tissue. This review article is based on the therapeutic outcomes of polymer-drug conjugates against breast and lung cancer.